Preclinical pharmacodynamic and pharmacokinetic characterization of the major metabolites of cariprazine - Kiss B; Némethy Z; Fazekas K; Kurkó D; Gyertyán I; Sághy K; Laszlovszky I; Farkas B; Kirschner N; Bolf-Terjéki E; Balázs O; Lendvai B (Dove Medical Press, 2019)
Béla Kiss, Zsolt Némethy, Károly Fazekas, Dalma Kurkó, István Gyertyán, Katalin Sághy, István Laszlovszky, Bence Farkas, Norbert Kirschner, Etelka Bolf-Terjéki, Ottilia Balázs, Balázs Lendvai Pharmacological and Drug Safety Research, Gedeon Richter Plc, Budapest, HungaryCorrespondence: Béla KissPharmacological and Drug Safety Research, Gedeon Richter Plc, P.O. Box 27, Budapest H-1475, HungaryTel +361 431 4226Fax +361 889 8400Email b.kiss@richter.huIntroduction: Cariprazine, a dopamine D3-preferring D3/D2 receptor partial agonist and serotonin 5-HT1A receptor partial agonist, has two major human metabolites, desmethyl-cariprazine (DCAR) and didesmethyl-cariprazine (DDCAR). The metabolite pharmacology was profiled to understand the contribution to cariprazine efficacy.Methods: In vitro receptor binding and functional assays, electrophysiology, animal models, microdialysis, and kinetic-metabolism approaches were used to characterize the pharmacology of DCAR and DDCAR. Results: Similar to cariprazine, both metabolites showed high affinity for human D3, D2L, 5-HT1A, 5-HT2A, and 5-HT2B receptors, albeit with higher selectivity than cariprazine for D3 versus D2 receptors. In [35S]GTPγS binding assays, cariprazine and DDCAR were antagonists in membranes from rat striatum and from cells expressing human D2 and D3 receptors, and were partial agonists in membranes from rat hippocampus. In cAMP signaling assays, cariprazine, DCAR, and DDCAR acted as partial agonists at D2 and D3 receptors; cariprazine and DDCAR were full agonists, whereas DCAR was a partial agonist at 5-HT1A receptors. Cariprazine, DCAR, and DDCAR were pure antagonists at human 5-HT2B receptors. Cariprazine and DDCAR increased rat striatal dopamine and reduced cortical serotonin turnover. Cariprazine and DDCAR showed similar in vivo D3 receptor occupancy in rat brain; however, cariprazine was more potent for D2 receptor occupancy. Both cariprazine and DDCAR dose-dependently but partially suppressed the spontaneous activity of midbrain dopaminergic neurons in rats, with the parent compound being more potent but shorter acting than its metabolite. Consistent with the D2 receptor occupancy profile, DDCAR was 3- to 10-fold less potent than cariprazine in rodent models of antipsychotic-like activity. Following acute cariprazine administration, DDCAR was detected in the rodent brain but at much lower levels than cariprazine.Conclusion: Overall, in vitro and in vivo pharmacological profiles of DCAR and DDCAR demonstrated high similarity with cariprazine, suggesting that the major metabolites of cariprazine contribute significantly to its clinical efficacy.Keywords: dopamine, serotonin, schizophrenia, bipolar disorder, desmethyl-cariprazine, didesmethyl-cariprazine